2017
DOI: 10.1039/c7ta02950k
|View full text |Cite
|
Sign up to set email alerts
|

Highly active and stable Er0.4Bi1.6O3 decorated La0.76Sr0.19MnO3+δ nanostructured oxygen electrodes for reversible solid oxide cells

Abstract: A directly assembled ESB decorated LSM nanostructured electrode exhibits high electrocatalytic activity and excellent stability in reversible solid oxide cell mode.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
45
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(48 citation statements)
references
References 71 publications
1
45
1
Order By: Relevance
“…The presence of the highly oxygen ionic conducting ESB layer at the interface not only improves the electrocatalytic activity of the LSCFNb cathode, but also promotes the rapid ion migration at the electrode/electrolyte interface. 49,78 The in situ formed ESB layer acts as a barrier layer to prevent the reaction between the segregated SrO and YSZ, inhibiting the formation of SrZrO3 at the cathode/electrolyte interface and thus preventing the further segregation of Sr (Figure 5a).…”
Section: Effects Of Polarization On Sr Segregation and Esb-lscfnb/yszmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of the highly oxygen ionic conducting ESB layer at the interface not only improves the electrocatalytic activity of the LSCFNb cathode, but also promotes the rapid ion migration at the electrode/electrolyte interface. 49,78 The in situ formed ESB layer acts as a barrier layer to prevent the reaction between the segregated SrO and YSZ, inhibiting the formation of SrZrO3 at the cathode/electrolyte interface and thus preventing the further segregation of Sr (Figure 5a).…”
Section: Effects Of Polarization On Sr Segregation and Esb-lscfnb/yszmentioning
confidence: 99%
“…47 It was reported that LSCF started to react with yttria stabilized bismuth oxide (YSB) at 650 o C, but by infiltrating YSB into LSCF scaffold followed by 600 o C sintering, the performance of the YSB-LSCF cell with proton conducting electrolyte was significantly enhanced, reaching a peak power density of 167 mW cm -2 at 550 o C. 48 Most recently, we have shown that the incorporation of ESB with LSM and Sm0.95Co0.95Pd0.05O3-δ (SmCPd) composite electrodes via a decoration technique without presintering process at high temperatures significantly enhances the performance of the cathode. [49][50] For example, an anode supported YSZ electrolyte cell with directly assembled ESB decorated LSM cathode exhibited a peak power density of 1.62 W cm -2 at 750 o C, and excellent operation stability in reversible solid oxide cell (SOC) modes for more than 200 h. 49 The decoration method has significant advantages over the conventional composite by mechanical mixing or infiltration techniques. Bismuth oxide based composite electrodes prepared by mechanical mixing require a high temperature pre-sintering step, 40,46,51 which can be detrimental to the phase and structural stability of bismuth oxide phase.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, we have shown the feasibility of applying directly assembled electrode on electrolyte without requiring further high temperature sintering, and the formation of electrode/electrolyte interface induced in situ by cathodic polarization [26][27][28][29][30][31][32][33][34][35]. In the case of LSM electrode and YSZ electrolyte, the initial results indicate that the electrochemical performance of cathodic polarization induced interface is comparable to that of the conventional pre-sintered electrodes, though the topography of the interface is very different, i.e.…”
Section: Introductionmentioning
confidence: 98%
“…There are two issues associated with the support strategy, however, one of which is the unfavourable changes to the electronic and geometric properties of Pt, and the other is the possible detachment of particles from the support, with both issues causing dramatic decreases to Pt catalyst activities [233][234][235][236][237]. In this regard, carbon nanotubes (CNTs) have [224]. h-i SEM micrographs of the fractured cross section of LSCF-infiltrated NiO-YSZ/ YSZ/LSCF-YSZ RSOFC and porous YSZ backbone.…”
Section: Noble Metal Catalystsmentioning
confidence: 99%
“…Based on this, the effects of Ni/Co ratios were evaluated in a recent study by Chrzan et al [220] for a yttria-stabilized zirconia backbone with a Ce 0. To address the low melting temperature and high activity of bismuth-based oxides, Ai et al [224] successfully synthesized a 40 wt% Er 0.4 Bi 1.6 O 3 decorated with La 0.76 Sr 0.19 MnO 3+σ (ESB-LSM) using a new gelation method. In this method, the pre-sintering step at conventional elevated temperatures was prevented and subsequently, these modifications led to improved current densities with peak power densities of 1.62, 0.32, 0.17, 0.40 and 0.20 W cm −2 being achieved at 750, 700, 650, 600 and 550 °C, respectively.…”
Section: Non-noble Metal Catalystsmentioning
confidence: 99%